Effects of sitagliptin on intrahepatic lipid content in patients with non-alcoholic fatty liver disease - Wang, Xingchun; Zhao, Bangfeng; Sun, Hang; You, Hui; Qu, Shen (Frontiers in Endocrinology, 2022)
Purpose: Dipeptidyl peptidase-4 inhibitors (DPP-4I), key regulators of the actions of incretin hormones, exert anti-hyperglycemic effects in type 2 diabetes mellitus (T2DM) patients. A major unanswered question concerns the potential ability of DPP-4I to improve intrahepatic lipid (IHL) content in nonalcoholic fatty liver disease (NAFLD) patients. The aim of this study was to evaluate the effects of sitagliptin on IHL in NAFLD patients. Methods: A prospective, 24-week, single-center, open-label, comparative study enrolled 68 Chinese NAFLD patients with T2DM. Subjects were randomly divided into 4 groups: control group who did not take medicine (14 patients); sitagliptin group who received sitagliptin treatment (100mg per day) (17 patients); metformin group who received metformin (500mg three times per day) (17 patients); and sitagliptin plus metformin group who received sitagliptin (100mg per day) and metformin (500 mg three times per day) (20 patients). IHL, physical examination (waist circumstances, WC; body mass index, BMI), glucose-lipid metabolism (fasting plasma glucose, FPG; hemoglobin A1c, Hb1A1c; triglycerides; cholesterol; alanine aminotransferase, ALT; aspartate aminotransferase, AST) were measured at baseline and at 24 weeks. Results: 1) WC and BMI were decreased significantly in all groups except control group (all P <0.05). 2) There was no statistically significant difference in IHL among the sitagliptin, metformin, and sitagliptin plus metformin groups before and after treatment(all P＞0.05). Only the metformin group showed a statistically significant difference in IHL before and after treatment(P＜0.05). 3) Sitagliptin treatment led to a significant decrease in FBG and HbA1c when compared with the control group (all P <0.01). Additionally, HhA1c was significantly decreased in the sitagliptin group when compared with the metformin group (P < 0.05). 4) HbA1c and FBG were decreased by 0.8% and 0.7 mmol/l respectively and the percentage of patients with HbA1c less than 7% was 65% with sitagliptin treatment. Conclusion: Sitagliptin improves abnormalities in glucose metabolism, but does not reduce the IHL in T2DM with NAFLD, indicating that sitagliptin might be a therapeutic option for treatment of NAFLD indirectly while not directly on IHL.